The Influence of Capital Structure, Liquidity, Asset Structure, and Asset Turnover to the Financial Performance of the Consumer Industry Sector In IDX - Kartika Hendra Titisari, Neti Rukma Rahayu, Siti Nurlaela & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
The capital market industry is undergoing rapid growth. The company in carryingout its operational activities, requires a large capital. To be able to obtain fundseasily, of course, the company must be in a healthy financial condition. Thishealthy condition is reflected in the companys financial performance. The newnessof this research is to conduct empirical test about the effect of capital structure,liquidity, asset structure and asset turnover to financial performance of consumerindustry sector in Indonesia Stock Exchange year 2014-2016. The difference withprevious research lies in the use of independent variables, the number of samplesused and the study period. This research is a quantitative research. The method ofanalysis in this research is multiple linear regression analysis. Partial test result (ttest) shows that the variable of capital structure (DER), liquidity (CR), and assetturnover (TATO) have significant effect to financial performance (ROA). Whilethe asset structure variable (FATA) has no significant effect on financialperformance (ROA).Keyword: ROA, DER, CR, FATA, TATO